Study of Situational Disaster Nursing in Community Preparedness for Tidal Water Disaster in Bahagia Village Pangkal Babu, Tanjung Jabung Barat Regency - Subandi, Andi; Noerjoedianto, Dwi; Mekeama, Luri (Universitas Aisyah Pringsewu, 2021)
Safe Community is a condition that is expected to guarantee a sense of security and health of the community by involving the active role of the entire community, especially in dealing with daily emergencies and during disasters. Bahagia Village has a high risk of tidal water disaster but has never been touched by preparedness disaster from the government, while the significant obstacles are diarrheal disease and common skin disease. there is no provision of counseling or motivating the community to prepare for disaster management. In Tanjung Jabung Barat Regency, there are 3 districts that are prone to disasters, one of which is Tungkal Ilir District 1. Tungkal Ilir 1 District is geographically located on the high seas and within a radius of 1 km from the sea. Based on the BNPB's RBI (Indonesian Disaster Risk) study, land within a radius of 2 km from the sea has a greater risk of disaster with various potential disasters. In the last 10 years, there have been at least 5 tidal water disasters in Tungkal Ilir 1 District, especially in Bahagia Village. This condition underlies the need for a situational study of disaster preparedness in Tanjung Jabung Barat Regency to improve disaster risk reduction (DRR) efforts in order to create a rural-based safe community. This study aims situational state of disaster nursing preparedness of the community around the tidal area in order to realize a disaster preparedness village. This research was conducted with a quantitative survey analysis research with a combination of phenomenological approaches. The sample in this study are 60 respondents, the sampling technique known as purposive sampling. the parameters measured are the level of knowledge, policies and guidelines, emergency response plans, resource mobilization, and disaster warnings. Parameters are measured by disaster preparedness scores. The results of this study show that based on the disaster preparedness score, Bahagia Village community has classified as very ready on knowledge parameter (80,06%),as not ready on policies and guidelines parameter (12,08%), as less ready on emergency response plan parameter (41,83%), as less ready on disaster warning (48,45%), and as not ready on mobilization resources parameter (16,67%).